USE OF FERAL PIGEONS (Columba livia) AS BIOMONITORS OF TRACE METAL POLLUTION IN LIMA, PERU - Guevara-Torres, Diego R. (2023)
Trace metals continue to generate environmental pollution problems because of their persistence in the environment, representing a hazard for living organisms. Although recent studies have reported trace metal environmental pollution in soils of some parts of Lima, there is still much about trace metal pollution that needs to be explored. Using feral pigeons (Columba livia) as biomonitor could facilitate rapid assessments of trace metal contamination in cities like Lima.  In this study, we determined the concentrations of lead (Pb), cadmium (Cd), zinc (Zn), copper (Cu), molybdenum (Mo), selenium (Se), iron (Fe) and strontium (Sr) in the liver of 21 pigeons from three sites with industrial, urban and rural land-use characteristics. Our results showed that when compared to the rural site, the concentrations of Pb, Zn, Cu, Se, Fe and Sr were significantly higher in both the industrial and urban sites. These findings suggest the existence of a trace metal concentration gradient with higher concentrations in both the industrial and urban sites. Such gradient is consistent with the land-use characteristics of each one of the three sites, corroborating the environmental pollution problems associated with them. Overall, our study provides powerful evidence of the use of feral pigeons as biomonitor of trace metal pollution in Lima and other cities from Peru and the world. To our knowledge, this is the first trace metals assessment done in pigeons in Peru.